Unveiling the Green Impact: Exploring the Nexus Between Trade Openness and Environmental Quality in South Africa - DINGISWAYO, Unathi; SIBANDA, Kin; DUBIHLELA, Dorah (International Journal of Environmental, Sustainability, and Social Science, 2023)
In light of the escalating concerns about environmental sustainability and the profound impact of international trade on environmental outcomes, the study's focal point was to empirically investigate the relationship between trade openness and environmental quality in South Africa from 1994 to 2018. In order to achieve the goal, the research utilized the Autoregressive Distributed Lag (ARDL) Bounds method and Granger causality test for analyzing data. The ARDL Bounds approach was chosen for its ability to examine both short-run and long-run relationships, while the Granger causality test provided insights into the direction of causality between the variables. This combination of robust econometric techniques enhances the reliability and depth of the study's findings, leading to a more comprehensive understanding of the complex relationship between trade openness and environmental quality in the country. The analysis results revealed a significant and positive relationship between trade openness and carbon emissions in the short and long run. The Granger causality test also indicated a unidirectional causality from trade openness to environmental quality. These implications are paramount for the South African government's policy formulation. In order to tackle the environmental issues that come with open trade, the government must put in place trade agreements that will enhance its ability to address these concerns efficiently. One crucial step is reducing trade barriers on environmental goods, facilitating increased access to green technologies at lower costs. Moreover, the government should prioritize enacting and enforcing strict environmental laws to avoid the "pollution haven hypothesis," which often affects low-income countries.